Development of Gene Therapy for Thalassemia - Nienhuis, Arthur W. (Cold Spring Harbor Laboratory Press, 2012)
Retroviral vector–mediated gene transfer into hematopoietic stem cells provides a potentially curative therapy for severe β-thalassemia. Lentiviral vectors based on human immunodeficiency virus have been developed for this purpose and have been shown to be effective in curing thalassemia in mouse models. One participant in an ongoing clinical trial has achieved transfusion independence after gene transfer into bone marrow stem cells owing, in part, to a genetically modified, dominant clone. Ongoing efforts are focused on improving the efficiency of lentiviral vector–mediated gene transfer into stem cells so that the curative potential of gene transfer can be consistently achieved.